2012
DOI: 10.1103/physreva.85.053836
|View full text |Cite
|
Sign up to set email alerts
|

Electron rest mass and energy levels of atoms in the photonic crystal medium

Abstract: Photonic crystals are periodic systems that consist of dielectrics with different refractive indices. They are designed to act on photons in contrast to semiconductor crystals whose periodicity affects the motion of electrons. Here we consider the interaction of an atomic electron with its own radiation field in the case when the atom is placed in air voids of a photonic crystal and is not in mechanical contact with the vibrational degrees of freedom of the dielectric host. A strong modification of this intera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…So our purpose is to investigate the effect of concentration ratio of reactant and duration of the reaction on the particle size, making possible creation of PC with predetermined characteristics. Our results are relevant for the experimental verification of the effect predicted by the authors in [5]. …”
supporting
confidence: 77%
“…So our purpose is to investigate the effect of concentration ratio of reactant and duration of the reaction on the particle size, making possible creation of PC with predetermined characteristics. Our results are relevant for the experimental verification of the effect predicted by the authors in [5]. …”
supporting
confidence: 77%
“…We do not, as a rule, use QM to discuss the orbit of the Moon. Surprisingly, even the proposition P 2 above is contextual: the effective mass of an electron in vacuo is measurably different to the effective mass of an electron in a crystal [14]. We point out that physicists such as Dirac have explored the notion that physical 'constants' depend on time.…”
Section: Contextmentioning
confidence: 84%
“…In Ref. [16], it has been shown that a strong modification of the electromagnetic interaction in photonic crystals results in the fact that the electron mass changes its value. Actually in this case, we deal with a quantum electrodynamical (QED) effect that does not manifest itself in the free space.…”
Section: Introductionmentioning
confidence: 99%